Examination of mixed sodium dodecyl sulfate – 1-butanol micelles with molecular dynamics - Illia Kononenko; Vladimir Farafonov (Вісник Харківського національного університету: Серія xімія)
Properties of mixed micelles composed of sodium n-dodecyl sulfate surfactant and 1-butanol co‑surfactant were examined using molecular dynamics simulation for three experimentally observed compositions. The aggregation number varied in the range of 30 to 64, and the co-surfactant content was 75 to 32 molecules, respectively. The composition of the bulk water – 1-butanol mixture matched the experimentally studied concentrations. All-atom potential models and explicit solvent were used in order to capture the most structural details. Such characteristics as micelle size, co-surfactant location, depth of water penetration were determined. The simulated micelles were found to have compact ellipsoidal shape, except of the most co-surfactant-rich ones, which were elongated. The equilibrium composition differed little from the initial one indicating consistence of the simulations. The co-surfactant molecules were observed in different positions: either situated on the surface of surfactant aggregate or having hydrocarbon tails immersed in it. Still, the hydroxyl groups stayed on the micelle surface and preserved contact with bulk solution. Water molecules were found penetrating the mixed micelles up to 0.3 – 1.0 nm from their center. Degree of counterion binding was estimated and its dependence on micelle composition was derived. It was found to decrease with the co-surfactant content in a non-linear manner. Specifically, for co-surfactant content up to 34% the counterion binding was almost similar to that of pure sodium n‑dodecyl sulfate micelles; the value gradually fade at higher 1-butanol content. Several positions of the boundary between bound and free counterions were considered. The approach proposed here may be employed for examination of other mixed micelles, as well.